Taxing Tobacco in Georgia : Welfare and Distributional Gains of Smoking Cessation - Fuchs Tarlovsky, Alan (World Bank, Washington, DC, 2020)
This paper analyzes the welfare and distributional impacts of increasing taxes on cigarettes in Georgia. Increasing taxes on tobacco is an effective measure to reduce smoking. According to some estimates, increasing tobacco taxes could save more than GEL 3.6 billion and 53 thousand lives over a 15-year period. However, concerns over potentially regressive effects on the poor are often raised. An Extended Cost Benefit Analysis (ECBA) is applied to simulate the welfare and distributional impacts of raising prices on cigarettes. Decile-specific price elasticities of demand are estimated to account for heterogenous behavioral responses of different income groups. Empirical estimations confirm that poorer households in Georgia tend to reduce consumption more intensely when faced with higher tobacco prices. The estimated magnitude and distribution of elasticities are comparable to peer countries. The simulations based on household survey data suggest that the long-term net distributional effects of increasing taxes on cigarettes in Georgia are likely progressive. Incorporating the indirect benefits of reduced smoking -- reductions in medical expenses and earnings from adverted premature deaths -- could bring small, albeit positive, income gains for large sectors of the population. The magnitude of those benefits is most significant among lower-income households, potentially contributing to lift them out of poverty.